Stability of a Lipase Extracted from Seeds of Pachira aquatica in Commercial Detergents and Application Tests in Poultry Wastewater Pretreatment and Fat Particle Hydrolysis - Polizelli, Patricia Peres; Facchini, Fernanda Dell Antonio [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP] (Hindawi, 2013)
A protein extract containing a plant lipase from oleaginous seeds of Pachira aquatica was tested using soybean oil, wastewater from a poultry processing plant, and beef fat particles as substrate. The hydrolysis experiments were carried out at a temperature of 40°C, an incubation time of 90 minutes, and pH 8.0-9.0. The enzyme had the best stability at pH 9.0 and showed good stability in the alkaline range. It was found that P. aquatica lipase was stable in the presence of some commercial laundry detergent formulations, and it retained full activity up to 0.35% in hydrogen peroxide, despite losing activity at higher concentrations. Concerning wastewater, the lipase increased free fatty acids release by 7.4 times and promoted the hydrolysis of approximately 10% of the fats, suggesting that it could be included in a pretreatment stage, especially for vegetable oil degradation.
Keywords: lipases; enzimas